Integration of Hindu Ecological Values in Social Science Education to Increase Environmental Awareness Among High School Students in the City of Mataram - Ida Bagus Made Arjana; Gde Eka Pudja Dyatmika; Srirahayu Puspawati (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2026)
This research aims to analyze the integration of Hindu ecological values in social studies learning and its influence on the environmental awareness of high school students in Mataram City. Additionally, this research identifies the challenges and opportunities in integrating Hindu ecological values into the curriculum, as well as measuring the extent to which students understand and accept these environmental values. The method employed in this research is a qualitative approach, utilizing case study techniques. Data were collected through in-depth interviews and direct observations. The research results indicate that integrating Hindu ecological values, particularly the Tri Hita Karana teachings, enhances students' environmental awareness. Although there are challenges related to religious diversity and students' diverse cultural backgrounds, as well as limited teacher training, there is a significant opportunity to develop a more inclusive curriculum grounded in universal ecological principles. This research also highlights the importance of teacher training to ensure the practical understanding and implementation of Hindu ecological values in education. This research contributes to the development of the Social Studies curriculum by integrating ecological values into environmental education.